Gut virome sequencing in children with early islet autoimmunity - Kramná, Lenka; Kolářová, Kateřina; Oikarinen, Sami; Pursiheimo, Juha-Pekka; Ilonen, Jorma; Simell, Olli; Knip, Mikael; Veijola, Riitta; Hyöty, Heikki; Cinek, Ondrej (Diabetes care, 2015)
OBJECTIVE: This study used next-generation sequencing (NGS) technologies to characterize the gut virome at the onset of islet autoimmunity. RESEARCH DESIGN AND METHODS: We conducted a case-control study nested within the Finnish Diabetes Prediction and Prevention (DIPP) cohort. The stool virome in 19 case children, who turned islet autoantibody positive before the age of 2 years and later developed clinical type 1 diabetes, and 19 tightly matched control subjects was analyzed using NGS performed from stool samples collected 3, 6, and 9 months before the onset of islet autoimmunity. Human virus findings were verified using real-time PCR. RESULTS: One or more human viruses were present in 10.4% and bacteriophages were in 54% of the samples. The virome composition showed no association with islet autoimmunity. NGS was less sensitive and specific than real-time PCR. CONCLUSIONS: The present data suggest no dramatic changes in the gut virome shortly before the emergence of islet autoimmunity and emphasize the need of verification of mass sequencing results when viral exposure is assessed in association studies.
Keywords: Feces; střeva; diabetes mellitus 1. typu; hyperglykemie; Male; Child, Preschool; kvantitativní polymerázová řetězová reakce; Viruses; Autoantibodies; Genotype; Infant; Child; viry; Autoimmunity; dítě; Case-Control Studies; mužské pohlaví; Real-Time Polymerase Chain Reaction; Langerhansovy ostrůvky; Hyperglycemia; předškolní dítě; autoimunita; lidé; ženské pohlaví; studie případů a kontrol; Humans; autoprotilátky; kojenec; genotyp; Diabetes Mellitus, Type 1; Islets of Langerhans; Intestines; Female; feces